Prognostic importance of congenital cataract morphology: A case report - İlhan, Çağrı (Journal of Surgery and Medicine, 2018)
Congenital cataract (CC) has an important place in pediatric ocular diseases. CCs are different from senile nuclear cataracts in terms of their etiologic, clinic and morphological characteristics. CCs occur many different forms such as non-hereditary isolated cases or autosomal dominant bilateral cases. In addition, many of ocular and systemic diseases can be associated with CC and ophthalmologist should be aware of these potential risks. In this article, we questioned whether the different morphological features of CC have prognostic importance or effect decision of surgery by considering a case of CC.